Peningkatan Minat Belajar Anak Usia Dini Menggunakan Alat Peraga Gambar - Hendro Hariyanto Siburian; Julia Galung (PEADA': Jurnal Pendidikan Kristen, 2022)
This study aimed to improve the problem of students' low interest in learning in the learning process in spiritual development lessons. This study uses a qualitative descriptive method with a classroom action research approach. The researcher found that the learning interest of class B, TK Perwita Asih Tawangmangu students in spiritual development lessons was low (initial observation). The research subjects were 14 students of class B, TK Perwita Asih Tawangmangu. The teaching’s aid in the form of pictures are used to explain learning concepts from abstract material to be real and clear, thus stimulating the senses of sight, thoughts, feelings, and attention of students. The results of the implementation of the improvement in learning interest in cycle 1 found 80 percent an increase in interest in learning and the results of the performance test of 82.1 percent. While in cycle 2, there was an increase in the learning interest of class B students in spiritual development lessons by 99.1 percent and the performance test score by 100 percent. In conclusion, there was an increase in the learning interest of class B students in spiritual development lessons through the application of visual aids in the form of pictures. Penelitian ini bertujuan untuk memperbaiki masalah rendahnya minat belajar peserta didik dalam proses pembelajaran pada pelajaran bina rohani. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan penelitian tindakan kelas. Peneliti menemukan bahwa minat belajar peserta didik kelas B, TK Perwita Asih Tawangmangu pada pelajaran bina rohani rendah (observasi awal). Subjek penelitian adalah 14 orang peserta didik kelas B, TK Perwita Asih Tawangmangu. Alat peraga berupa gambar dapat digunakan untuk menjelaskan konsep-konsep pembelajaran dari materi yang bersifat abstrak menjadi nyata dan jelas, sehingga merangsang indra penglihatan, pikiran, perasaan, dan perhatian peserta didik. Hasil pelaksanaan tindakan perbaikan minat belajar pada siklus 1 ditemukan 80 persen terjadi peningkatan minat belajar dan hasil tes unjuk kerja sebesar 82,1 persen. Sedangkan pada siklus 2, terjadi peningkatan minat belajar peserta didik kelas B pada pelajaran bina rohani sebesar 99,1 persen dan nilai tes unjuk kerja sebesar 100 persen. Kesimpulannya, terjadi peningkatan minat belajar peserta didik kelas B pada pelajaran bina rohani melalui penerapan alat peraga berupa gambar.